Continuing series of innovations by entrepreneurship to perform competitive resilience in airline business - Sukardi, Samudra; Wahyuni, Sari; Rachmawati, Riani (International Journal of Innovative Research and Scientific Studies, 2025)
The unprecedented pandemic has impacted the airline industry, thus requiring strategic entrepreneurship to facilitate competitive resilience and long-term performance. This study investigated the value chain of an airline by exploring the relationships between entrepreneurship, innovation capability, organizational innovation, digital collaboration, and business model innovation, to build competitiveness and become resilient. The research study employed a quantitative and cross-sectional design while collecting data through structured questionnaires from top executives of an airline, with success eventually affecting all senior executives in the country. The principal results of hypothesis analysis were obtained using “Smart Partial Least Square Structure Equation Model” (SPLS SEM) software. It was found that entrepreneurship capability has an accepted indirect effect on competitive resilience within the research model. The results showed that triple series innovation serves as an important mediator that connects entrepreneurship capability to building competitive resilience. Specifically, dimensions of variables like self-efficacy, industry dynamics, and risk-taking portrayed significant levels of validity and reliability. Entrepreneurship capability and competitive resilience act as measures of a robust industry in its ability to weather the storms of volatility caused by the pandemic. These findings highlight the need for aligning entrepreneurship capability with technology and the value chain to stay competitive in a dynamic market. The study intended to add empirical evidence to entrepreneurship capability in the aviation domain by uncovering interdependencies between triple series innovation dimensions to foster competitive resilience.